6x+2(x+5)=-2X-8

Simple and best practice solution for 6x+2(x+5)=-2X-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2(x+5)=-2X-8 equation:


Simplifying
6x + 2(x + 5) = -2X + -8

Reorder the terms:
6x + 2(5 + x) = -2X + -8
6x + (5 * 2 + x * 2) = -2X + -8
6x + (10 + 2x) = -2X + -8

Reorder the terms:
10 + 6x + 2x = -2X + -8

Combine like terms: 6x + 2x = 8x
10 + 8x = -2X + -8

Reorder the terms:
10 + 8x = -8 + -2X

Solving
10 + 8x = -8 + -2X

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 8x = -8 + -10 + -2X

Combine like terms: 10 + -10 = 0
0 + 8x = -8 + -10 + -2X
8x = -8 + -10 + -2X

Combine like terms: -8 + -10 = -18
8x = -18 + -2X

Divide each side by '8'.
x = -2.25 + -0.25X

Simplifying
x = -2.25 + -0.25X

See similar equations:

| 15x+30=12-10x-20 | | 32x^2+13=40x | | 1.5x=.6x-9 | | 32x^2+13-40x=0 | | 4(5x+3)=10(2x+5) | | 2x^2-80x-273=0 | | H(x)=-3x^2+-12x+4 | | H(x)=-3x^2+-12x | | g+1.1=20 | | b+12.89=0.89 | | H(x)=-3x^2-12x | | 6.8=2d | | .75x-9=27 | | k+5.56=-13.44 | | -2u=-9.8 | | 6(2x-4)=12(x+3) | | 821=r+111 | | 821=r+11 | | f-622=-8 | | m^2-8m-12=0 | | s+-239=-512 | | q-38=666 | | q-38=66 | | -9b=45 | | g+36=63 | | -55=f-92 | | 15-2x=7x+23 | | w-1.48=2.22 | | G(x)=36-4x^2 | | n+3=9.82 | | 3b=-1.2 | | g+195=780 |

Equations solver categories